2020
DOI: 10.1108/ajim-02-2020-0054
|View full text |Cite
|
Sign up to set email alerts
|

Identifying gaps in using artificial intelligence to support students with intellectual disabilities from education and health perspectives

Abstract: PurposeStudents with developmental/intellectual disabilities (ID/DD) often have serious health issues that require additional medical care and supervision. Serious health issues also mean increased absence and additional lags in academic achievement and development of adaptive and social skills. The incorporation of artificial intelligence in the education of a child with ID/DD could ameliorate the educational, adaptive and social skill gaps that occur as a direct result of persistent health problems.Design/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…For example, it has been reported that OpenAI's GPT-3 language model [78] exhibits bias in terms of displaying strong associations between Muslims and violence [79]. There are many more other examples of biased results in AI [77,[80][81][82][83][84].…”
Section: Biasmentioning
confidence: 99%
“…For example, it has been reported that OpenAI's GPT-3 language model [78] exhibits bias in terms of displaying strong associations between Muslims and violence [79]. There are many more other examples of biased results in AI [77,[80][81][82][83][84].…”
Section: Biasmentioning
confidence: 99%
“…Some studies, including studies [5,9,12], in regard to the legal and ethical aspects of applying artificial intelligence systems in the medical field have shown that ethical tools are not sufficient to ensure that artificial intelligence is used ethically and legal systems must be updated to meet new challenges and emerging in the field of artificial intelligence. Also, it is possible that the risks become legal afterwards such as who is given consent and who bears responsibility in the event of an unfavorable development?…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Among these obstacles, we would mention the legal concern. Study [5] mentioned that the obstacle that may prevent the application of AI is that it lacks appropriate regulations and some political, ethical and financial transformations. Does the current legislative framework seem appropriate to regulate artificial intelligence in terms of safety and efficiency?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AI can become an active force for the reduction of inequalities (e.g., (Capucha et al 2020)), incorporating a concept of distributive justice that looks at marginal categories as subjects of priority intervention. Tools based on AI, for example, can be useful, within the educational system, to bridge learning gaps (Drigas and Ioannidou 2013;Kharbat et al 2021), while in the health care sector, they can be used to stimulate social empowerment and services for individuals with disabilities (Neto et al 2019). From the perspective of the Italian Constitution, the impact on work, employment and wages primarily requires due attention.…”
Section: Inequality Reductionmentioning
confidence: 99%